Microcomputers and Mathematics in Schools. A Discussion Paper - Fletcher, T. J.; Department of Education and Science, London (England). ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1983)
This paper is addressed to those who are concerned with the development of the school curriculum as a whole and to those who have a particular interest in mathematics. The aim is to promote discussion between these two overlapping groups, so that the growing use of computers in mathematics can be coordinated with developments in other areas of the curriculum. The paper resulted from a series of visits to schools in England by one of Her Majesty's Inspectors. Topics discussed include the basis for the school curriculum; the place of mathematics in the curriculum; the Cockcroft report; current uses of computers in schools at both elementary and secondary levels; types of uses, including drill and practice, short and simple programs, and games; student reactions; background on computer studies; projects; computer familiarization; mathematics and other subjects; the relationship of mathematics with computers; and the implications for mathematics teaching and for resources, staffing, and in-service training. (MNS)
Practitioners.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Computer Oriented Programs; Educational Planning; Elementary Secondary Education; Mathematics Curriculum; Mathematics Education; Mathematics Instruction; Microcomputers; England; Opinion Papers